Diffraction From Elastomeric Replicas of Philippine Weevil Surface Features - De Vera, Michie Vianca D (Archīum Ateneo, 2020)
Biomimetic components inspired by structures found in nature have led to enhanced performance and novel applications in numerous optical systems. Replicating biological nano- and microscale features typically requires complex and expensive fabrication methods. We make use of soft lithography to copy surface features found on two Philippine weevil species: Pachyrrhynchus congestus pavonius and Pachyrrhynchus congestus ocellatus. Microscopy reveals circular scales on the carapace of P. c. pavonius with an average diameter of 0.0651 mm. Similar scales are found on P. c. ocellatus, with a mean diameter of 0.0639 mm. Iridescence effects are observed in both species. Peak reflectance for the dorsal side of P. c. pavonius shifts from 631.31 to 601.37 nm with a 30 deg change in viewing angle. With an equivalent change in viewing angle, the dorsal side of P. c. ocellatus exhibits a reflectance peak transition from 558.37 to 510.13 nm. Customized molds are constructed that allow the forming of elastomeric casts of the ventral and dorsal surfaces of both weevil types using polydimethylsiloxane (PDMS). Micrographs of the PDMS replicas confirm that surface features are copied faithfully for both species. The elastomeric copy of P. c. ocellatus (dorsal) is scanned with a 50 mW, 514 nm Ar+ laser beam focused by a lens with focal length 5 cm. Diffraction patterns comprising a central maximum with concentric rings are generated. The biomimetic cast shows promise as an alternative diffractive element for generating circular patterns with variable intensity profiles.